A Hepatitis A Outbreak Caused by Implicated Ice from a Factory in Bueng Kan Province, Thailand, 2012 - Saritapirak, Nipapan; Waisaen, Chamnan; Juntee, Kittiphich; Singkham, Phathai; Monpangtiem, Kannika; Diregpoke, Borwornwan; Buathong, Rome (Journal of Health Science of Thailand, 2017)
The objective of this study was to investigate a suspected hepatitis A outbreak in Bueng Kan province between June and August 2012 in order to confirm the diagnosis, identify the transmission source and risk factors of the disease, and determine appropriate control measures. It was carried out as a descriptive study including patients’ interview, physical examination and laboratory analysis. A matched case-control study was performed to identify the transmission source and risk factors of the disease. It was found that a total of 1,272 cases including 241 suspected, 850 probable and 181 confirmed cases of hepatitis A were reported in the outbreak. The male to female ratio was 1.5 : 1. The age of the patients ranged between 2 and 69 years old with a median of 18 years. Clinical features of the cases were jaundice (100.0.%), fever (86.3%), dark urine and abdominal discomfort (76.6%). The first 5 cases from Muang and Bung Kla districts had onset on 14 June 2012. Subsequent cases were reported from other districts in the province, showing continuous common source outbreak. The hepatitis A virus with similar DNA patterns of the patients was identified from the water, ice, and stool samples of workers of one factory. A matched case-control study revealed significant association between the disease and consumption of ice produced from this factory by univariate analysis (matched odds ratio [OR] = 2.55, 95% confidence interval [CI] = 1.13- 5.73) and multivariate analysis (adjusted OR = 3.66; 95% CI = 1.34– 9.98). Control measures included closing the factory and hygienic improvement of the manufacturing processes. However, ice was illegally produced at night in the factory for sale and accounted for a number of subsequent cases. The factory owner was arrested and the outbreak rapidly curtailed after this legal measure.